Skin Cancer May Delay Onset but Not Progression of Parkinson's Disease: A Nested Case-Control Study - Mahajan, Abhimanyu; Chirra, Martina; Dwivedi, Alok K.; Sturchio, Andrea; Keeling, Elizabeth G.; Marsili, Luca; Espay, Alberto J. (Frontiers in Neurology, 2020)
Objective: To evaluate the extent to which cancer, a biological opposite to neurodegenerative disorders, may affect the onset and progression of Parkinson's disease (PD). Methods: A nested case-control design in consecutive PD patients with (cases) vs. without (controls) cancer was used to compare time to clinical diagnosis and time to Hoehn & Yahr (H&Y) staging score ≥ 3 as a measure of progression. Further, we compared PD onset and progression between cases with cancer diagnosis before (cancer before PD group) and after (cancer after PD group) PD onset. Independent variables were age at PD onset, motor subscale of the Movement Disorders Society-Unified Parkinson's Disease Rating Scale, sex, cognitive impairment, falls, depression, anxiety, dementia, and autonomic symptoms. Time to H&Y ≥ 3 was determined using Cox proportional hazards, with adjusted results summarized as hazards ratio (HR). Group differences were evaluated using unpaired t-test or Fisher's exact test. Results: The clinical PD onset was later in cases vs. controls (median 67.2 vs. 59.8 years; p < 0.001), but the adjusted time to H&Y ≥ 3 was similar between groups (HR = 0.67; p = 0.13). Skin cancers constituted 75% of all cancers in cases. Amongst skin cancers, compared to controls, cases had an older age at PD onset (67.8 vs. 59.8 years; p < 0.001). There was no difference in risk of progression in PD patients with skin cancer compared to controls (HR = 0.54, p = 0.09). Conclusions: Cancer, in particular of the skin, may delay the onset but not the progression of PD. Future prospective observational studies are warranted to elucidate the complex interactions between these biologically divergent disorders.